Ethnopharmacology study of medicinal plants utilization for antidiarrheal remedies by Tengger tribe in Tosari District, Indonesia - Ningsih, Indah Yulia; Mandasari, Virda Fitra; Pratama, Antonius Nugraha Widhi; Hidayat, Mochammad Amrun (Pharmaciana, 2024)
Tengger is one of the tribes in East Java Province, Indonesia practising traditional medicine by using mantras and medicinal plants. A disease with a high incidence rate and widely treated with medicinal plants in Indonesia, including in Tosari District, Pasuruan Regency, is diarrhoea. To conserve traditional medicine, mainly the utilization of medicinal plants as anti-diarrhoea agents, it is necessary to develop a database that keeps up with technological advances. The study aimed to determine medicinal plants utilization for antidiarrheal remedies by the Tengger tribe in four villages of Tosari District, Pasuruan Regency, namely Wonokitri, Tosari, Ngadiwono, and Podokoyo. The study employed the snowball sampling method, which involved conducting semi-structured interviews. The result showed nine medicinal plants for traditional antidiarrheal remedies, with Musaceae (23%) as the most widely used plant family. Most informants used immature plant (56.25%) and fruits (89.58%). In addition, most plants were administered orally (98%) without specific compounding methods (76%). The value of Factor of the informant's consensus (Fic) of plants used for diarrhoea was 0.74. The highest Fidelity Level (FL) and Choice Value (CV) were obtained from Elaeocarpus longifolius Blume at 69% and 2.4, respectively. Based on the findings of the study, E. longifolius has the potential to be further investigated for development in antidiarrheal treatment.